Fiber Wireless testbed using Universal Software Radio Peripheral (USRP) - Ridwan M.A.; Radzi N.A.M.; Abdullah F.; Din N.M.; Al-Mansoori M.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer peripheral equipment; Fibers; Network architecture; Optical communication; Passive optical networks; Radio communication; Testbeds; Communication platforms; Fiber-wireless; Fiberwireless (FiWi); Lab VIEW; National Instruments; Software-defined radios; Universal software radio peripherals (USRP); USRP; Software radio